Exploring the Teachers’ Lived Experience in Using Code-Switching within EFL Setting in West Borneo - Siboro, Efrika; Agung, Antonius Setyawan Sugeng Nur (ENGLISH JOURNAL, 2022)
Exploring teacher experience in teaching English as a foreign language is always unique and challenging especially when it is seen as the perception of the native English teachers. The purpose of this research is to explore the native English teachers’ lived experience towards their perceptions on using code-switching in teaching English to Indonesian students in West Borneo. The respective participants belong to non-profit organization focussing on English education. Obtaining the data, this study used open-ended questions and guided interview. This study reflects the usages and functions of code-switching. The usages of Code Switching are to speed up the explanation of difficult concepts, build rapport between students and teachers, help to explain new vocabulary, and increase teachers’ understanding towards students’ L1, and become a tool to enhance evaluate students’ comprehension on towards the lesson. While the linguistic function helps the teachers in two ways: first is to enhance the students’ understanding of the target language and the second is to build rapport between students and teachers. The affective function is considered beneficial to arise students’ motivation and willingness to study English.